dPob/EMC is essential for biosynthesis of rhodopsin and other multi-pass membrane proteins in Drosophila photoreceptors. - Satoh, T.; Ohba, A.; Liu, Z.; Inagaki, T.; Satoh, A.K. (eLife, 2015)
In eukaryotes, most integral membrane proteins are synthesized, integrated into the membrane, and folded properly in the endoplasmic reticulum (ER). We screened the mutants affecting rhabdomeric expression of rhodopsin 1 (Rh1) in the Drosophila photoreceptors and found that dPob/EMC3, EMC1, and EMC8/9, Drosophila homologs of subunits of ER membrane protein complex (EMC), are essential for stabilization of immature Rh1 in an earlier step than that at which another Rh1-specific chaperone (NinaA) acts. dPob/EMC3 localizes to the ER and associates with EMC1 and calnexin. Moreover, EMC is required for the stable expression of other multi-pass transmembrane proteins such as minor rhodopsins Rh3 and Rh4, transient receptor potential, and Na(+)K(+)-ATPase, but not for a secreted protein or type I single-pass transmembrane proteins. Furthermore, we found that dPob/EMC3 deficiency induces rhabdomere degeneration in a light-independent manner. These results collectively indicate that EMC is a key factor in the biogenesis of multi-pass transmembrane proteins, including Rh1, and its loss causes retinal degeneration.